Multivariate integer cycle-slip resolution: A single-channel analysis - Teunissen, Peter; de Bakker, P. (2016)
In this contribution we study the strength of the single-receiver, single-channel GNSS model for instantaneously resolving integer cycle-slips. This will be done for multi-frequency GPS, Galileo and BeiDou, thereby focusing on the challenging case that the slip is due to a simultaneous loss of lock on all frequencies. The analytical analysis presented is supported by means of numerical results.